Specialized educational service in the public network: intervention strategy in a case of double exceptionality (Research, Society and Development, 2023)
Among the diversity of students in the school context, there are those who still have little identification in the regular classroom, including Double Exceptionality (DE), that is, Asperger Syndrome (AS) and High Abilities (AH). Due to gaps in the initial and continuing education of teachers that enable them to recognize the characteristics of specific human talents, the biggest harmed in this situation is the student. Qualitative research where the object researched is the trajectory of the student XD (fictitious name) in the school environment. The type of study is a single case study, which places the case as the focus of research. The Medical Evaluation showed a clearly above average position in intellectual capacity and a higher average than expected for their age and education, with a percentile equal to or better than 40% for a group of their same age group; his cognitive development presented some distortions with delays, his academic performance being impaired due to limitations in social interactions, in addition to severe blocks in relation to the environment, with reactions to pressure, anxiety, inadequate feelings, which made him highly attached to their imaginations and fantasy, bringing the feeling of a dangerous, uncertain, rigid, inflexible world. In this case, communication increased as trust was established and it was possible to perceive the set of experiences of the subject of the report from the stimulus of a game, since playfulness had a positive part in this process linked to difficulties. The ability of oral communication was stimulated with gamification and graphic representation, stimulated by the interest in the English language. The partnership with an institution with a gamification and robotics project greatly facilitated the development of XD as an individual in society, strengthening ties, affirming trust and opening up new professional horizons. A private actor, Coordinating Professor of the Pedagogical Nucleus, and the collaboration of the entire school community leveraged and underpinned XD’s educational inclusion.